Implications of the Changes in the System of National Accounts for Measured Growth and the Business Cycle - Patrick Vanhoudt (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2002)
The recent changes in the national accounts unequivocally imply that the nature of the measured growth rate and business cycle has changed. This note investigates to what extent.
Keywords: E32; O47; O51; 330; Business cycle; national accounts; software expenditures; Volkswirtschaftliche Gesamtrechnung; Definition; Konjunktur; Wirtschaftswachstum; Software; EU-Staaten; USA